ANALISIS KESIAPSIAGAAN SEKOLAH DASAR DALAM MITIGASI BENCANA GEMPA BUMI: STUDI DI SDN SINDANGKERTA - Ai Ismatul Muhibah; Anggit Merliana; Pidi Mohamad Setiadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Elementary schools play a strategic role in equipping students with basic understanding and skills related to disaster preparedness. This study aims to describe the implementation of earthquake disaster mitigation at SDN Sindangkerta in Tasikmalaya, focusing on facilities, disaster management, and the integration of disaster education. The research method used was descriptive qualitative, with subjects consisting of the principal, teachers, and students. Data were obtained through interviews and analyzed using the Miles and Huberman interactive model, which includes data collection, data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of disaster mitigation at this school remains at a basic level. In terms of facilities, evacuation routes and assembly points are limited and lack supporting facilities such as early warning systems and adequate safety equipment. In terms of disaster management, there are no clear procedures or systems, and evacuation simulations are not conducted regularly. Meanwhile, in terms of education, disaster material has not been integrated into the curriculum, resulting in low student skills in responding to emergencies. These findings emphasize the need for improvements through upgrading facilities, establishing a structured disaster management system, and strengthening disaster education in elementary schools.